Protein-protein interaction of cytochrome b561 in chromaffin vesicle membranes studied by two-dimensional blue-native/sodium dodecyl sulfate gel electrophoresis and co-immunoprecipitation analysis - Takeuchi, Fusako (Acta Biologica Szegediensis, 2006)
We analyzed a protein-protein interaction in solubilized chromaffin vesicles using two-dimensional electrophoresis (1st, Blue-Native PAGE; 2nd, Tricine-SDS-PAGE). Cytochrome b561 band, which was verified by immunoblotting, was observed in the two-dimensional gel with an apparent molecular weight of 100 400kDa. On the other hand, purified cytochrome b561 showed a monomeric band (28 kDa) in Blue-Native PAGE. These results indicated that cytochrome b561 interacts with other proteins in the chromaffin vesicles to form a large protein complex(es). To clarify the nature of the interaction, we performed co-immunoprecipitation experiments, where the solubilized membrane proteins were treated with immunopurified anti- b561 IgG antibodies followed by sedimentation with protein-A-Sepharose. We found that there were no other proteins co-sedimented with cytochrome b561. Since the immunopurified anti- b561 IgG antibodies bound specifically to the C-terminal hydrophilic portion of cytochrome b561 protein, we concluded that such binding of the IgG antibodies to the C-terminal portion might cause an inhibition of protein-protein interaction with other proteins in the solubilized state.